THE ROLE OF LITERATURE IN SHAPING SOCIAL CONSCIOUSNESS: PAST AND PRESENT - Mundafale, Aachal (International Journal of Research -GRANTHAALAYAH, 2015)
Literature has never just been a way to show off one's imagination; it is a powerful force that changes, reflects, and critiques society. Literary works have been used for moral questioning, political dissent, cultural preservation, and social change throughout history and across cultures. Literature is both a mirror and a lamp. It shows us how things are and how they could be better, from ancient epics to modern digital stories. This article looks at how literature has changed people's minds about social issues in the past and present, showing how it can change minds across time and cultures.